PITYOPHAGUS QUERCUS REITTER, 1877, A NEW SAPROXYLIC SAP BEETLE FOR THE ITALIAN FAUNA (Coleoptera, Nitidulidae) - Audisio, Paolo; Chiari, Stefano; Zauli, Agnese; Jansson, Nicklas; Carpaneto, Giuseppe Maria (Fragmenta entomologica, 2011)
During ecological investigations on saproxylic beetle communities of central Italy (Latium), at Bosco Polverino (a mixed evergreen/deciduous forest fragment dominated by cork oaks), and at Allumiere (a small fragment of beech forest surrounded by turkey oak stands), the authors found three specimens of Pityophagus quercus Reitter, 1877 (Coleoptera, Nitidulidae). These are the first known records of this species in Italy, and the first one in association with an evergreen oak, Quercus suber. This discovery led us to review both bionomical and faunistic data so far available on this exceedingly rare and poorly known species.